The Effect Of Profitability And Tax Avoidance On Firm Value With The Moderating Role Of Board Of Directors’ Gender Diversity - Hambra, Nawat Qisthi Al-Izzatil; Rachman, Helmy Aulia (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
This study aims to provide empirical evidence on the effect of return on assets (ROA), return on equity (ROE), and tax avoidance on firm value, as well as the moderating role of board of directors’ gender diversity in these relationships. The background of this research is based on studies examining the effect of profitability and tax avoidance on firm value, which have reported mixed findings. The data were obtained from 51 non-cyclical consumer sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period and analyzed using multiple linear regression and moderated regression. The results show that ROA has a significant effect on firm value, ROE has a significant effect on firm value, and tax avoidance has a significant effect on firm value. Furthermore, board of directors’ gender diversity does not moderate the effects of ROA, ROE, and tax avoidance on firm value.